COMPARISON OF HYPOXIC INDUCIBLE FACTOR 1 ALPHA (HIF1α) BETWEEN GASTRITIS POSITIVE AND NEGATIVE HELICOBACTER PYLORI - Risna Wati, GontarAlamsyah Siregar & Dharma Lindarto (International Journal of Research Science and Management, 2020)
Introduction: Gastritis is a conditions with inflammation of the lining of the stomach. Helicobacterpylori (H.pylori) is the main etiology of chronic gastritis. Hypoxic Inducible Factor (HIF) is a transcription factor involved in adaptation to low oxygen conditions. HIF also prolongs the life of neutrophils by inhibiting the apoptotic pathway. HIF has a role in inflammatory signals. Aim: To determine the ratio of HIF1-α levels in gastritis patients with positive and negative H.pylori with blood samples from HIF1-α not from the gastric mucosa. Methods: This study was cross sectional design was conducted on 80 people with gastritis, diagnosed histopathologically based on examination of tissue taken during a gastroscopy. H. pylori was examined by CLO method and HIF levels by ELISA sandwich method using Invitrogen HIF-1 Alpha Elisa Kit. Data analysis was performed using the Mann Whitney Test. Result: Significant differences were found where HIF-1α levels in positive H. pylori were higher than negative H. pylori (p <0.05). Conclusion: There were significant differences between HIF-1α levels in positive and negative H.pylori.